Estimation of vitamin B12 in plasma by High Performance Liquid Chromatography (Bangladesh Journal of Pharmacology, 2017)
High performance liquid chromatography was used to develop and validate the detection of vitamin B12 in blood plasma sample. The mobile phase consists of a mixture of 0.025% trifluroacetic acid in deionized water and 30% methanol. The mixture used was adjusted to pH 2.9 and the flow rate was adjusted to 0.5 mL/min. The separation was achieved using C18 column maintained at 30ºC temperature and detection of vitamin B12 was conducted at maximum wavelength 230 nm.Video Clip of Methodology:Estimation of vitamin B12 in plasma by HPLC: 4 min 29 sec   Full Screen   Alternate